Strategi Guru PAI dalam Membentuk Akhlak Berkomunikasi Siswa Di SMP Budi Utomo Binjai - Oktariani, Cindy; Sapri, Sapri (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to identify and describe the strategies used by Islamic Religious Education (IRE) teachers to shape students' communication ethics at SMP Budi Utomo Binjai, as well as analyze the implementation of these strategies in students' daily communication, including in the digital era. The methodology used is qualitative with a focus on phenomenology, including observation, interviews, and documentation. The findings show that IRE teachers use various strategies, including role-modeling, habituation, discussion, lectures, reprimand, motivation, use of digital technology, and collaboration with teachers. Based on these findings, the use of digital technology is found to be an integral part of the teachers' strategy. Furthermore, the study reveals that contributing factors to the success of ethical communication include teacher role-modeling, teamwork, and active student participation. Meanwhile, inhibiting factors can be seen through the decline in students' awareness and the role of parents. This study recommends developing teachers' creativity in digital learning and fostering collaboration between schools and students to optimize student communication in the modern era.